2023
DOI: 10.2147/jhc.s396433
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Based on Platelet–Albumin–Bilirubin for Predicting Tumor Recurrence After Surgery in Alpha-Fetoprotein-Negative Hepatocellular Carcinoma Patients

Abstract: Purpose In this study, we developed a nomogram based on the platelet–albumin–bilirubin (PALBI) score to predict recurrence-free survival (RFS) after curative resection in alpha-fetoprotein (AFP)-negative (≤20 ng/mL) hepatocellular carcinoma (HCC) patients. Patients and Methods A total of 194 pathologically confirmed AFP-negative HCC patients were retrospectively analyzed. Univariate and multivariate Cox regression analyses were performed to screen the independent risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Numerous inflammatory, nutritional, and immune indicators, including GAR, GAPR, AAR, ALBI, LMR, NrLR, CRP, and PALBI, have been linked to the prognosis of patients with AFP-NHCC. 24 , 27–29 , 31 However, these individual indices are insufficient for patient risk stratification. Previous studies have demonstrated the prognostic efficacy of a composite score combining inflammation, immunity, and nutrition in intrahepatic cholangiocarcinoma; 47 however, such a study is lacking in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous inflammatory, nutritional, and immune indicators, including GAR, GAPR, AAR, ALBI, LMR, NrLR, CRP, and PALBI, have been linked to the prognosis of patients with AFP-NHCC. 24 , 27–29 , 31 However, these individual indices are insufficient for patient risk stratification. Previous studies have demonstrated the prognostic efficacy of a composite score combining inflammation, immunity, and nutrition in intrahepatic cholangiocarcinoma; 47 however, such a study is lacking in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous inflammatory, nutritional, and immune indicators, including GAR, GAPR, AAR, ALBI, LMR, NrLR, CRP, and PALBI, have been linked to the prognosis of patients with AFP-NHCC. 24,[27][28][29]31 However, these formulated LFNII scores incorporated these nine indicators. Earlier studies identified ANRI, ALRI, AAPR, SII, and SIRI as indicators of inflammatory immune status in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation